The impact of urban residential noise and air pollution on youth mental health: a scoping review - Siti Norain Sallahuddin,; Rosnah Sutan,; Mohd Hasni Jaafar, (Universiti Kebangsaan Malaysia, 2025)
Urban noise and air pollution contribute indirectly to mental health disorders, particularly among adolescents and young adults, due to their ongoing neurodevelopment and increased exposure to environmental pollutants. Hence, it is crucial to understand the impact of urban environmental pollution on youth's mental health. This scoping review was conducted to evaluate the impact of urban air and noise pollution on youth mental health. Articles published between January 2014 and October 2024 were identified through four databases (PubMed, Scopus, Web of Science, and ProQuest), using terms such as noise pollution, air pollution, mental health, and youth. Studies involving urban youth and mental health as an outcome were included. Data from eligible studies were synthesized to identify patterns and gaps in the literature. Fourteen studies (n = 14) were included out of 1555 records retrieved. Long term exposure to air pollutants, such as PM 2.5, PM 10, and NO2, were consistently associated with negative mental health outcomes, including poor mental health (PM2.5: OR 1.19, 95% CI 1.03-1.38; NO2: OR 1.23, 95% CI 1.04-1.38; PM10: OR 1.07, 95% CI 0.98-1.17); depression and anxiety (PM2.5: OR 1.24, 95% CI 1.12-1.38; PM10: OR = 1.87, 95 % CI 1.69–2.07); and internalising symptoms. Short-term exposure also contributed to indirect mental health burden through increased emergency visits and increased psychotropic medications. Findings were heterogeneous for noise pollution, with short-term exposure linked to generally poor mental health, whereas long-term exposure was associated with depression, anxiety, and suicidal risk in some studies. The review highlights the significant effect of urban air and noise pollution on youth mental health. Targeted and effective interventions, including urban planning, environmental regulations, and youth-focused public health strategies, are necessary to mitigate these negative effects.